Evaluation of the in vitro antioxidant and antitumor activity of hydroalcoholic extract from Jatropha mollissima leaves in Wistar rats - Iqbal, Muhammad Omer; Gu, Yuchao; Khan, Imran Ahmad; Wang, Ruihong; Chen, Jin (Frontiers in Chemistry, 2023)
Introduction: Despite modern sciences and advancements in new drugs or chemicals, the new era now rushes natural remedies for various illnesses and diseases that lead to end organ damage. In this study, we investigated Jatropha mollissima ethanolic extract’s effect against doxorubicin-induced cardiotoxicity and renal toxicity. Methods: To determine phytochemicals, a phytochemical screening was conducted. Various assays were used to measure the antioxidant activity, including the DPPH (2,2-diphenylpicrylhydrazyl), SOD (superoxide dismutase), NO (nitric oxide), and others. The antiproliferative effect of Jm was assessed by MTT assay; morphological analysis was performed using an inverted and phase contrast microscope, ultra morphological analysis of apoptosis with acridine orange (AO)/propidium iodide (PI) staining. Results: It was seen that doxorubicin caused elevated serum markers and abnormal changes in histological patterns. The significant reduction in cardiac and renal marker levels seen in groups given either 400 or 600 mg/kg of crude extract demonstrates that Jm has a protective effect against doxorubicin-induced cardiotoxicity due to the presence of active phytoconstituents having antioxidant potential. There is a dose-dependent decrease in cell viability when using J. mollissima. Apoptosis was observed in the treated cells. Conclusion: In conclusion, our research lends credence to the idea that J. mollissima could be used for cancer management and have cardioprotective and nephroprotective effects.